Effect of floor tiles on the behaviour of slabs - Dillah, D.N (Universiti Malaysia Sarawak, UNIMAS, 2009)
Floor tiles might always been assumed as the aesthetical value on the slab. There are various types of floor tiles available in the market. The quality of the floor tiles are depending on how it is being manufactured and also the type of the tile itself. For this study purposes, the strength of the floor tiles especially the compressive strength are discovered. Floor tile in this study was just as an aesthetical value but it to enhance the strength of the slab. The analysis of this study is to find the difference in term of strength, ultimate moment and deflection values between the slab without floor tiles and the slab after the installation of floor tiles. The experimental testing on both slabs had been conducted and as a result, the slab with addition of floor tiles on obtained the higher strength than the slab without the floor tiles. Other than experimental testing, manual calculation in designing the slab was taken into account too. The manual calculation was in accordance to the BS8110 : Part 1 : 1985. The analysis of the design also shows that slab with the floor tiles cast on it has higher ultimate moment as compared with the normal slab. Both of the testing and calculation prove that floor tiles help to increase the strength of the slab.